The effect of fly ash suspension as coolant in milling process - Kanis, Finiks (2023)
The removal of material from the workpiece as well as the alteration of its surface are both components of the milling process, which is a series of procedures. When working with metal, almost all of the available energy is converted into heat during the cutting process. During the milling process, the area where the cutting tool and the workpiece come into contact generates a zone of extremely high temperatures. This happens because the milling process involves the removal of material. As a direct consequence of this, the surface quality of the workpiece suffers as a whole. Consequently, the utilisation of a coolant is necessary to resolve this issue. This research project, evaluated how the machining of mild steel is affected by the use of a variety of different cooling techniques. Experiments were conducted using a standard milling setup, comparing the performance of palm oil with and without fly ash as an additive on surface roughness and cutting forces during machining processes. Various cutting parameters including cutting speed, feed rate, and depth of cut were investigated using the Taguchi method. The results demonstrated that the addition of fly ash to palm oil significantly improves surface roughness and reduces cutting forces compared to pure palm oil. The optimum parameters for surface roughness are A2 (palm oil with fly ash), B1 (feed rate 600 mm/min), C3 (cutting speed 1800rpm) and D2 (depth of cut 0.3mm). whereas the optimum parameters for cutting force are A2 (palm oil with fly ash), B1(feed rate 600 mm/min), C1 (cutting speed 1000rpm) and D1 (depth of cut 0.2mm). The findings of this study contribute to the development of environmentally friendly lubrication strategies in the manufacturing industry, utilizing waste materials to improve machining performance and sustainability.